2022
DOI: 10.1177/00274321221114869
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Universal Design Principles in Music Teaching

Abstract: Students with disabilities (SWDs) in the United States have a right to the least restrictive learning environment as enshrined in federal law. Until recently, conceptions about educating SWDs have drawn from medical models of disability (i.e., that the student must be accommodated to interact with the environment) rather than a social model of disability (i.e., that the environment can be cultivated for all kinds of individual needs). Universal Design for Learning (UDL) is an educational framework that music e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…To reach large numbers of students in relatively short amounts of instructional time, it is critical for educators to select highly effective strategies. In addition, these strategies must be accessible to students with a wide array of learning needs.Music education scholars (Armes et al, 2022;Darrow, 2010;Draper, 2022;Salvador & Culp, 2022) have suggested universal design for learning (UDL) (CAST, 2016) as an approach for critically considering music instruction and ensuring equitable access to all students. UDL is an educational framework focused on removing barriers and providing support to enable all students to be successful in the classroom (CAST, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To reach large numbers of students in relatively short amounts of instructional time, it is critical for educators to select highly effective strategies. In addition, these strategies must be accessible to students with a wide array of learning needs.Music education scholars (Armes et al, 2022;Darrow, 2010;Draper, 2022;Salvador & Culp, 2022) have suggested universal design for learning (UDL) (CAST, 2016) as an approach for critically considering music instruction and ensuring equitable access to all students. UDL is an educational framework focused on removing barriers and providing support to enable all students to be successful in the classroom (CAST, 2016).…”
mentioning
confidence: 99%
“…Music education scholars (Armes et al, 2022; Darrow, 2010; Draper, 2022; Salvador & Culp, 2022) have suggested universal design for learning (UDL) (CAST, 2016) as an approach for critically considering music instruction and ensuring equitable access to all students. UDL is an educational framework focused on removing barriers and providing support to enable all students to be successful in the classroom (CAST, 2016).…”
mentioning
confidence: 99%